Low‐grade oncocytic tumour of the kidney is characterised by genetic alterations of TSC1, TSC2, MTOR or PIK3CA and consistent GATA3 positivity. Issue 2 (18th October 2022) - Williamson, Sean R; Hes, Ondrej; Trpkov, Kiril; Aggarwal, Aditi; Satapathy, Abhishek; Mishra, Sourav; Sharma, Shivani; Sangoi, Ankur; Cheng, Liang; Akgul, Mahmut; Idrees, Muhammad; Levin, Albert; et al.
Abstract : Low‐grade oncocytic tumour (LOT) of the kidney has recently emerged as a potential novel tumour type. Despite similarity to oncocytoma or eosinophilic chromophobe renal cell carcinoma, it shows diffuse keratin 7 immunohistochemistry (IHC) and negative KIT (CD117), which differs from both. We aimed to identify the molecular characteristics of these tumours. Seventeen tumours (one male, 16 female, nine previously published) fitting the original description of this entity (solid eosinophilic cell morphology, often with areas of tumour cells loosely stretched in oedematous stroma, and the above IHC features) were analysed with a next‐generation sequencing panel of 324 cancer‐associated genes from formalin‐fixed, paraffin‐embedded tissue. All tumours harboured at least one alteration in either TSC1 ( n  = 7, 41%), TSC2 ( n  = 2, 12%), MTOR ( n  = 5, 29%) or PIK3CA ( n  = 4, 24%). Four tumours harboured a second alteration, including two NF2, one each in conjunction with MTOR and  TSC2 alterations, one PTEN with TSC1 alteration and one tumour with both MTOR and TSC1 alterations. No other renal cancer‐related or recurring gene alterations were identified. In addition to the previously described IHC findings, 16 of 16 were positive for GATA3. Eleven patients with follow‐up had no metastases or recurrent tumours. Recurrent tuberous sclerosis/MTOR pathway gene alterations in LOT support its consideration as a distinct morphological, immunohistochemical and genetic entity. PIK3CA is another pathway member that may be altered in these tumours. Further study will be necessary to determine whether tumour behaviour or syndromic associations differ from those of oncocytoma and chromophobe carcinoma, warranting different clinical consideration. Abstract :